Stability and Dynamical Analysis of a Biological System - Xinhong Pan; Min Zhao; Yapei Wang; Hengguo Yu; Zengling Ma; Qi Wang (Abstract and Applied Analysis)
This study considers the spatiotemporal dynamics of a reaction-diffusion phytoplankton-zooplankton system with a double Allee effect on prey under a homogeneous boundary condition. The qualitative properties are analyzed, including the local stability of all equilibria and the global asymptotic property of the unique positive equilibrium. We also discuss the Hopf bifurcation and the steady state bifurcation of the system. These results are expected to help understand the complexity of the Allee effect and the interaction between phytoplankton and zooplankton.